Genetic variants in immune mediators as potential molecular biomarkers for oral cancer evaluation: Insights from a systematic revaluation by computational analyses and Bayesian approaches - Juliana Campos Botelho; Samuel Arcebispo Brasileiro; André Victor Oliveira Monteiro; Alessandro Luiz Araújo Bentes Leal; Naum Neves da Costa dos Santos; Gabrielly Ribeiro Alves; Reyce Santos Koga; Haline Alves da Silva; José Rogério Souza Monteiro; Denis Vieira Gomes Ferreira; Adenilson Leão Pereira; Ana Carolina Alves de Oliveira; et al. (Oral Oncology Reports)
Background: Oral cancer is a complex disease in which genetic variations in immune mediator play a relevant role in its pathophysiology. This study aimed at assessing the level of false-positive rates on meta-analytic data on genetic variations in immune mediator genes related with oral cancer risk. Material and methods: A systematic search was performed for meta-analyses in this field that were published before September 22, 2024. The calculations for the False-Positive Rate Probability (FPRP) and the Bayesian False Discovery Probability (BFDP) were performed to assess the noteworthiness with a statistical power of 1.2 and 1.5 of Odds Ratio (OR) at a prior probability of 10−3 and 10−6. A methodological evaluation by the Venice criteria was performed and in silico networks were designed. Results: Ten meta-analyses on the TNFA/rs361625/rs1800629, VEGF/rs3025039, IL4/rs2070874, IL6/rs1800795, IL8/rs4073 and IL10/rs1800896 genes/polymorphisms and oral cancer have been included. 88 significant OR association values from the meta-analyses included allowed the performance of 336 calculations for FPRP and 176 for BFDP. We found 35 noteworthy values (10.42 %) for FPRP and 59 noteworthy values (33.52 %) for BFDP that demonstrated the variants in VEGF and IL10 with noteworthiness association with oral cancer. The gene-gene and protein-protein networks evidenced the role of VEGF, TNFA, IL4, IL6, IL8 and IL10 genes in the physiopathology of the disease. Conclusions: The Bayesian calculations and the in-silico analyses indicated the rs3025039 and rs1800896 polymorphisms in the VEGF and IL10 genes, respectively, as noteworthy molecular biomarkers for oral cancer risk evaluation.